PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK MENGGUNAKAN FLIPBUILDER PADA MATERI LINGKUNGAN SAHABAT KITA - Firda Azizah Hafiz; Nurlinda Safitri; M. Ginanjar Ganeswara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is the main key in determining the high and low of human resources, to face the development of the era in this fast-paced global era, education strives to help students to be able to do their tasks in life independently, there are always developments in the world of education including learning media. Therefore, it is necessary to develop learning media that vary according to the needs and conditions of students. This development research uses the ADDIE method which consists of five stages, namely Analysis, design, development, implementation, and evaluation. The observation place was carried out at SDN Panaragan 2 Bogor City. Information collection was conducted by interviews and questionnaire assessments from media experts, linguists, material experts, and student response questionnaires. The results of product development are flipbook learning media for our friends' environmental materials. The results of expert validation research get a percentage of 100% with the category "feasible". In the limited test phase, as many as 25 students received a very good response with a percentage of 96% with the category "feasible". Based on the results of the study, it can be concluded that the flipbook learning media of our friends' environment material in this study has proven to be valid, interesting, easy to use and feasible to be applied as a learning tool.